The Characteristics of Blood Pressure Variability in Subjects with Chronic Kidney Disease Stage III in Diabetic or Non-diabetic Patients - Aleksandrovna, Klitsunova Yuliia (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: Тhe aim of this study was to understand the relationship between circadian rhythm of blood pressure (BP) and renal function characteristics in subjects with chronic kidney disease (CKD) Stage III of diabetic and non-diabetic etiology. Materials and Methods: A total of 30 CKD - hypertensive patients without diabetes and 30 Type 2 diabetic patients with overt diabetic nephropathy (DN) were enrolled in this study. The values of BP variability were obtained from 24 h ambulatory BP monitoring. Results: As a result of a comprehensive examination of patients and statistical processing of data, it was found that in the group of patients with DN the level of albumin to creatinine in the urine was significantly higher than in the group of patients with non-DN (4.08 ± 6.15) mg/g and (1.43 ± 2.94) mg/g, respectively, significantly higher than triglycerides compared with the group of non-DN (2.72 ± 1.53) mmol/L and (1.55 ± 1.14) mmol/L, respectively. An interesting regularity was that patients with non-DN had a tendency to drop their BP in the morning, and thus the morning rise in systolic BP (SBP) and diastolic BP (DBP) in this group of patients was negative (−4.88 ± 21.35) mm Hg and (−70.88 ± 14.35) mm Hg, respectively. In patients with DN, these parameters exceed the norm and make up for SBP (66.02 ± 21.48) mm Hg and for DBP (57.13 ± 12.75) mm Hg. The mean daily diastolic pressure in the group of patients with DN was significantly higher than in the group of non-DN ([124.50 ± 33.78] and [111.50 ± 11.5] mm Hg, P < 0.05), the SBP variability was significantly lower than in the group with non-DN (13.67 ± 2.99) mm Hg and (16.35 ± 3.69) mm Hg, respectively. Severe disturbances in the circadian rhythm of arterial pressure with low BP variability, high rates, and rates of morning ascent of SBP and DBP were characteristic of the group of DN. Conclusions: In patients with DN with comparable values of glomerular filtration rate, higher albumin to creatinine ratio, lipid profile disorders were significantly more frequent than in the group of patients with the non-diabetic renal disease. The mean daily diastolic pressure in the group of patients with DN was significantly higher than in the group of non-DN ([124.50 ± 33.78] and [111.50 ± 11.5] mm Hg, P < 0.05), the SBP variability was significantly lower than in the group with non-DN (13.67 ± 2.99) mm Hg and (16.35 ± 3.69) mm Hg, respectively.